2006
DOI: 10.1177/1049731505285453
|View full text |Cite
|
Sign up to set email alerts
|

Do Master’s in Social Work Programs Teach Empirically Supported Interventions? A Survey of Deans and Directors

Abstract: Objective: A questionnaire to examine efforts toward the teaching of empirically supported interventions (ESI) was mailed to the 165 deans and directors of Council on Social Work Education-accredited Master’s in social work (MSW) programs; 66 (40%) responded. Method: Questions included program characteristics and items assessing both faculty and official program positions on ESI, which were summed to provide scores as an index of commitment to ESI. Results: Informal faculty commitment to teaching ESI was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Authors of a related investigation concluded that "while the profession may continue to struggle to define EBP, it is hard to justify the lack of training in psychotherapies that are supported by clear research evidence and a seeming preference for those lacking the support of research evidence" (Bledsoe et al, in press). Woody, D'Souza, and Dartman (2006) also recently reported less than encouraging findings from a survey of social work deans and directors (or their designees) examining whether and how their programs teach empirically supported interventions. They observed that only 31 programs, less than half, had endorsed teaching specific ESI [Empirically Supported Interventions] content; still fewer, 26, had designated courses to teach specific ESI content; and of the 31 programs that had endorsed teaching ESI, very small numbers required ESI training materials designed for teaching students the skills and techniques for implementing the interventions.…”
Section: Contemporary Social Work Graduate Educationmentioning
confidence: 94%
See 1 more Smart Citation
“…Authors of a related investigation concluded that "while the profession may continue to struggle to define EBP, it is hard to justify the lack of training in psychotherapies that are supported by clear research evidence and a seeming preference for those lacking the support of research evidence" (Bledsoe et al, in press). Woody, D'Souza, and Dartman (2006) also recently reported less than encouraging findings from a survey of social work deans and directors (or their designees) examining whether and how their programs teach empirically supported interventions. They observed that only 31 programs, less than half, had endorsed teaching specific ESI [Empirically Supported Interventions] content; still fewer, 26, had designated courses to teach specific ESI content; and of the 31 programs that had endorsed teaching ESI, very small numbers required ESI training materials designed for teaching students the skills and techniques for implementing the interventions.…”
Section: Contemporary Social Work Graduate Educationmentioning
confidence: 94%
“…They observed that only 31 programs, less than half, had endorsed teaching specific ESI [Empirically Supported Interventions] content; still fewer, 26, had designated courses to teach specific ESI content; and of the 31 programs that had endorsed teaching ESI, very small numbers required ESI training materials designed for teaching students the skills and techniques for implementing the interventions. (p. 474) Woody et al (2006) cautiously concluded that "the present sample is not overrepresented by programs with faculty who are visibly or highly engaged with the EBP movement" (pp. 474-475).…”
Section: Contemporary Social Work Graduate Educationmentioning
confidence: 96%
“…Regarding organizational factors that affect the perception of barriers toward the diffusion of EBPs in educational programs, researchers from the aforementioned disciplines have noted such things as (a) program type (i.e., master's‐granting programs vs. doctoral‐granting programs; Woody, D'Souza, & Dartman, 2006); (b) accreditation status (i.e., CACREP accreditation vs. non‐CACREP accreditation; Hoge, Tondora, & Stuart, 2003; Scott, 2000); and (c) faculty position (i.e., core faculty [e.g., full professors, associate professors, assistant professors] vs. noncore faculty [e.g., visiting instructor, adjunct, lecturer]; Beasley & Woolley, 2002; Rubin & Parrish, 2007).…”
mentioning
confidence: 99%
“…In order for this collaboration to succeed, faculty must partner with agency administrators, practitioners, and field educators in a more comprehensive and systematic way. Those social work educators in academic and field settings with expertise and experience in the use of evidence-based practice models are well positioned to lead the training effort needed which can ultimately benefit the profession by providing clients and communities with effective services (Woody et al 2006). …”
Section: Curricula Renewal Revision and Expansionmentioning
confidence: 99%
“…Wheeler and Goodman (2007) believe that social work students need additional skills in the retrieval, evaluation, and synthesis of information for decision-making in clinical social work practice. Woody et al (2006) address the importance for field supervisors and instructors to be actively involved in curriculum development and agency-based training in evidence-based practice and evidence-supported interventions. Finally, Howard et al (2007) advocate that schools of social work provide field instructors with training in evidence-based practice methods and provide access to websites with links to searchable computerized bibliographic databases in order to enhance the ability of social work students to deliver treatments that are supported by research evidence.…”
Section: Curricula Renewal Revision and Expansionmentioning
confidence: 99%